Designing Organizational Management and Blockchain-based Information System Architecture in the Bamboo Creative Industry Center - Ikhwana, Andri; Setiawan, Ridwan; Wardhani, Zamilla Putri (Universitas Atma Jaya Yogyakarta, 2025)
Indonesia boasts a wide range of bamboo species and is among the largest manufacturers of bamboo in Asia. However, the Garut Bamboo Creative Industry Center, one of Indonesia's bamboo industries, encounters various challenges in managing this industry. This study is assumed to recognize the need for adaptation to changing times and more efficient management in the bamboo industry supply chain. The aim is to design an organization management and information system architecture based on blockchain technology. The methodology applied the Star Model and prototyping approach, leading to the development of a strategy, an association-based organizational structure, structured business processes, a balanced reward system, and the placement of human resources based on their qualifications. It enables product tracking and increases operational efficiency by integrating blockchain technology into warehouse and production information systems. It also proposes innovative solutions to ensure growth and sustainable development. The study suggests recommendations, including implementing blockchain technology as a product management and supply chain enhancement solution to support the bamboo company's growth and aspirations.